2014
DOI: 10.1017/s0031182013002035
|View full text |Cite
|
Sign up to set email alerts
|

Conventional PCR for molecular diagnosis of human strongyloidiasis

Abstract: Strongyloidiasis is frequently asymptomatic and diagnosis of latent infection is difficult due to limitations of current parasitological and serological methods. This study aimed to verify the use of conventional polymerase chain reaction (PCR) assay for molecular diagnosis of Strongyloides stercoralis infection. Fresh stool samples were obtained from 103 individuals: 33 S. stercoralis positive, 30 positive for other parasites and 40 negative for parasitological methods. These samples were examined by the Lutz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
(59 reference statements)
1
27
1
7
Order By: Relevance
“…the 18S rRNA small subunit (SSU); the internal transcribed spacer region 1 (ITS-1); the 28S rRNA gene; or the cyclooxygenase gene (cox1) 19,[23][24][25][26][27][28][29][30][32][33][34][35][36][37] . Published sensitivities and specificities for…”
Section: Pcrmentioning
confidence: 99%
See 3 more Smart Citations
“…the 18S rRNA small subunit (SSU); the internal transcribed spacer region 1 (ITS-1); the 28S rRNA gene; or the cyclooxygenase gene (cox1) 19,[23][24][25][26][27][28][29][30][32][33][34][35][36][37] . Published sensitivities and specificities for…”
Section: Pcrmentioning
confidence: 99%
“…Studies have also assessed the specificity of the PCR products by sequence analysis, with all finding 100% sequence homology with the target sequence of S. stercoralis. 24,25,27,29 . Sitta et al found a number of false positives, using published genus and species-specific primers, based on non-target sized bands on gel electrophoresis 19,25 .…”
Section: Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…A PCR tem sido mencionada como uma metodologia auxiliar, com alta sensibilidade e especificidade para o diagnóstico molecular de S. stercoralis (Repetto et al, 2013;Sitta et al, 2014). A detecção de DNA do parasito em amostras fecais através da amplificação por PCR em tempo real (qPCR) utilizando iniciadores referentes ao gene ribossomal, mostrou-se sensível e específico Kramme et al, 2011).…”
Section: Diagnóstico Molecularunclassified